Functional Consequences for Apoptosis by Transcription Elongation Regulator 1 (TCERG1)-Mediated Bcl-x and Fas/CD95 Alternative Splicing - Montes, Marta (PLoS One, 2015)
Here, we present evidence for a specific role of the splicing-related factor TCERG1 in regulating apoptosis in live cells by modulating the alternative splicing of the apoptotic genes Bcl-x and Fas. We show that TCERG1 modulates Bcl-x alternative splicing during apoptosis and its activity in Bcl-x alternative splicing correlates with the induction of apoptosis, as determined by assessing dead cells, sub-G1-phase cells, annexin-V binding, cell viability, and cleavage of caspase-3 and PARP-1. Furthermore, the effect of TCERG1 on apoptosis involved changes in mitochondrial membrane permeabilization. We also found that depletion of TCERG1 reduces the expression of the activated form of the pro-apoptotic mitochondrial membrane protein Bak, which remains inactive by heterodimerizing with Bcl-x(L), preventing the initial step of cytochrome c release in Bak-mediated mitochondrial apoptosis. In addition, we provide evidence that TCERG1 also participates in the death receptor-mediated apoptosis pathway. Interestingly, TCERG1 also modulates Fas/CD95 alternative splicing. We propose that TCERG1 sensitizes a cell to apoptotic agents, thus promoting apoptosis by regulating the alternative splicing of both the Bcl-x and Fas/CD95 genes. Our findings may provide a new link between the control of alternative splicing and the molecular events leading to apoptosis.